Factors Affecting Buying Decision of Women in Online Cosmetic Products Shopping in India - Akhil Ganjoo (International Journal of Advanced Science and Technology, 2020)
Many Indian industries have truly benefitted from the revolutionary introduction and amalgamation of e-commerce into their businesses and have utilized it to sell their products by changing their mode of product distribution from brick and mortar stores to online e-commerce platforms. Be it electronics, grocery, clothing and footwear industry or for that fact even the pharmaceutical industry, all of them have been very welcoming to utilize this means to gain an edge in terms of customer acquisition and driving their sales. On the other hand, ample opportunities for women on the professional front and their exposure to the internet services since the availability of round the clock internet services in the Indian context has helped them build confidence, feel empowered and given them a sense of feeling valued about their decision-making ability. On top of it, their familiarity with advances in technology, be it using cell-phones or the internet for their benefit has given the cosmetics industry in India a reason to change their conventional selling behavior of ‘touch, feel and smell’ which was only possible at a retail outlet to going online and taking that extra risk of pushing their product line on e-commerce sites. This study, which is exploratory in nature aims at finding out what are various factors which influence the buying behavior of these women and exploring various consumer preferences which these women have developed by using the medium of digital shopping. This study will gather insights beneficial to the cosmetic industries which have so much to learn and implement from their customers who have upgraded themselves using the internet services which are now available at disposal. This study aims at exploring the benefits of e-commerce like round the clock shopping, setting delivery preferences, variety, setting pricing strategies and above all the access of information to their best use so that customer inclination towards the online mode of purchase can be bigger than ever. This study seeks to understand the factors influencing customer’s motivation and decision to shop cosmetic products online. Statistical tool like multiple linear Regressions was applied to test the developed propositions and hypotheses. The four determinants viz; convenience of shopping online, quality of the cosmetic products, variety of brands available and discounts and cash back available online have been found to have significant effect on a customer’s decision to shop cosmetic products online.